RANCANG BANGUN MEDIA BUKU DIGITAL MATERI ARTI LAMBANG GARUDA PANCASILA KELAS III SEKOLAH DASAR - Shofi Nurafifah; Dinie Anggraeni Dewi; Yayang Furi Purnamasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is motivated by the lack of use of learning media, especially in the Civics Class III elementary school subjects, and there are difficulties in understanding the meaning of the Garuda Pancasila symbol because the material is quite a lot but the media used is still less attractive. So that students quickly feel bored and less active in participating in PPkn learning. The purpose of this study is to determine the design of digital book media for the meaning of the Garuda Pancasila symbol. This study uses the Design and Development (D&D) method with the ADDIE model (Analysis, design, development, implementation, and evaluation). The results of this study resulted in a product in the form of a digital book media material meaning the Garuda Pancasila symbol for grade III elementary school. In designing digital book media, it is carried out through two stages including the analysis and design stages. The analysis stage is the initial stage to determine user needs for learning media. The design stage is carried out to design and create digital book media material about the meaning of the Garuda Pancasila symbol according to user needs based on the results of the analysis that has been carried out.